Study of the bacteriome of nodules from native mexican beans: characterization and selection of plant growth promoting bacteria - Ortega Esparza, Cinthya Judith (Universidad Autónoma Chapingo, 2026)
In Mexico, the common bean (Phaseolus vulgaris L.) is a strategic crop due to its nutritional, economic, and sociocultural significance. Like other legumes, it can establish symbiotic relationships with nitrogen-fixing bacteria; however, the role of other bacteria associated with this process remains underexplored, despite their potential to enhance agricultural productivity and plant health. This study aimed to characterize these populations and their metabolism using metabarcoding techniques and in vitro assays to identify strains with potential as biofertilizers. Samples from two contrasting ecological regions were compared: a semi-arid zone (Durango) and a humid subtropical zone (Guerrero). Functional results revealed that environmental origin significantly influences the metabolic capabilities of the isolates: those from the humid region exhibited higher enzymatic activity (proteases and amylases), while siderophore production was more prevalent in the semi-arid region. Outstanding strains, such as G9 and D7, were selected for their notable capacity to produce ammonium, indole-acetic acid, and siderophores. Furthermore, molecular analyses confirmed that while the genus Rhizobium is the most abundant, the nodules harbor a diverse consortium of non-rhizobial bacteria, predominantly within the phyla Proteobacteria and Bacteroidota. In improved varieties from the northern region, a "conserved microbial core" was identified, as no significant differences in bacterial diversity were observed among the evaluated genotypes. This study demonstrates that both the environment and host selection model the architecture of the nodule microbiome. These findings contribute to the transition from synthetic fertilizer dependence toward the strategic utilization of native bacterial diversity.
Tesis (Maestría en Ciencias en Recursos Naturales y Medio Ambiente en Zonas Áridas)
Keywords: Phaseolus vulgaris, nodules, metabarcoding, rhizobia